The governance of sustainable city business models - Nolden, C (European Council for an Energy Efficient Economy, 2019)
This paper analyses how sustainability and climate action relating to mobility, buildings and energy networks are governed in European cities. To this end, different modes of governance for sharing burdens, costs and risks of innovative low-carbon experiments, projects and demonstrations in ten European cities in seven countries are compared.